Multilevel surgery in adults with cerebral palsy - Putz, Cornelia; Döderlein, Leonhard; Wolf, Sebastian Immanuel; Gantz, Simone; Braatz, Frank; Dreher, Thomas (The bone & joint journal, 2016)
Aims Single-event multilevel surgery (SEMLS) has been used as an effective intervention in children with bilateral spastic cerebral palsy (BSCP) for 30 years. To date there is no evidence for SEMLS in adults with BSCP and the intervention remains focus of debate.MethodsThis study analysed the short-term outcome (mean 1.7 years, standard deviation 0.9) of 97 ambulatory adults with BSCP who performed three-dimensional gait analysis before and after SEMLS at one institution. ResultsTwo objective gait variables were calculated pre- and post-operatively; the Gillette Gait Index (GGI) and the Gait Profile Score (GPS). The results were analysed in three groups according to their childhood surgical history (group 1 = no surgery, group 2 = surgery other than SEMLS, group 3 = SEMLS). Improvements in gait were shown by a significant decrease of GPS (p = 0.001). Similar results were obtained for both legs (GGI right side and left side p = 0.01). Furthermore, significant improvements were found in all subgroups although this was less marked in group 3, where patients had undergone previous SEMLS. DiscussionSEMLS is an effective and safe procedure to improve gait in adults with cerebral palsy. However, a longer rehabilitation period is to be expected than found in children. SEMLS is still effective in adult patients who have undergone previous SEMLS in childhood.Take home message: Single-event multilevel surgery is a safe and effective procedure to improve gait disorders in adults with bilateral spastic cerebral palsy.Cite this article: Bone Joint J 2016;98-B:282-8.
Gesehen am 27.01.2021